Factor that Influence Lactation on Postpartum Mother - Lilis Mamuroh; Sukmawati S; Yanti Hermayanti; Furkon Nurhakim (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Breastfeeding is a natural process as a mother’s responsibility to take care of her baby. The natural process of lactation started during pregnancy. During pregnancy, breast is prepared therefore when the baby is born, the mother can breastfeed her newborn soon. The purpose of this research is to discover the relationship between breast care, lactation, breastfeeding techniques that related to lactation, and calories and protein consumption that related to lactation. Research method used in this study is description. Population for this research is hospitalized postpartum mothers in Kalimaya Room dr Slamet Regional Public Hospital Garut which amounts to 96 people and the sample mehod used is total sampling. Based on the research’s result from 96 people showed that did poor breast care treatment was 27.08%, good treatment was 50.00% and did a very good breast care treatment was 22.9%. Of the 96 people that performed improper breastfeeding techniques was 32.29%, performed proper breastfeeding technique was 54.17%, performed a very appropriate breastfeeding technique was 13.54%. Based on the results of the study, out of 96 people, who got less calorie intake from the needs was 8.33% and who got calorie intake from the needs was 91.67%. Of 96 people showed that who got protein intake from the needs was 100% which means they got the necessary nutritional intake. There are still plenty of postpartum mother in Kalimaya Room dr Slamet Garut Regional Public Hospital that has problem with lactation.Keywords: Breastfeeding, Lactation, Postpartum Period